Supervision of Staff-performance at Work Level - Tuladhar, Subarna Man (Administration and Management Review, 2009)
Office supervision for improved delivery of public service involves statutory and other functions viz., setting performance goals, planning work-schedule, analyzing jobs, selecting persons for jobs and training, controlling and coordinating operations, maximizing human potential, disciplining subordinates, motivating employees, monitoring and directing group efforts, keeping up with organizational goals, appraising performance and so on. The governments' poor performance in and outside ministries is all realized. In order to rectify the deteriorating performance situation of the government offices, periodic supervisory checks over the service performance of office staff is quite essential. Present article attempts to highlight some aspects of supervision which are crucial in one regard namely projecting enhanced image of the government in its service delivery mechanismAdministration And Management Review Vol 20, No.2 August 2008 Page: 44-56